PARTIAL PURIFICATION OF DEXTRANASE ENZYME FROM STREPTOCOCCUS SOBRINUS - SATHYA G.; PALANISWAMY M. (International Journal of Pharma and Bio Sciences, 2013)
In the present investigation, the crude dextranase enzyme obtained from S. sobrinus was purified by ion- exchange chromatographic technique using DEAE- cellulose. The final purification fold 20.58 and 4.7% recovery was obtained. Molecular weight of 50 kDa was determined by SDS- PAGE.